Role of CT in detection of Gall Bladder lesions A Radiographic Study - Anil Kumar Bansal; Anil Kumar Gupta (Asian Journal of Medical Radiological Research, 2020)
Background: Carcinoma of the gall bladder (GB) is the fifth most common malignancy of the gastrointestinal tract and the commonest malignancy of the biliary tree. The present study was conducted to assess the efficacy of CT scan in detection of gall bladder lesions.Subjects and Methods: The present study was conducted on 76 patients of both genders. CT Scan was performed in all patients.Results:Out of 76 patients, males were 42 and females were 34. Common lesions were gall bladder CA in 20, distal cholangio CA in 20, GB mass in 24 and cholelithiasis in 12. The difference was significant (P< 0.05). The sensitivity of CT was 98% and specificity was 96%.Conclusion: Authors found that CT is useful in detection of gall bladder lesions.